Sintering process simulation of a solid oxide fuel cell anode and its predicted thermophysical properties. (October 2017) - Fu, Pei; Yan, Min; Zeng, Min; Wang, Qiuwang
Highlights: A CG-MD method is improved to simulate the sintering process of SOFC anode. Nanostructure and relevant thermal properties of the sintered anode are obtained. Effects of sintering conditions and composition are systematically investigated. Analyses and predictions provide a guide to obtain the desired properties. Abstract: Complex porous structure and properties of a solid oxide fuel cell (SOFC) anode significantly affect the SOFC performance. In this study, the sintering process of the typical NiO-YSZ anode is simulated by a coarse-grained molecular dynamics method. After the sintering process simulation, the porous nanostructure is obtained and the thermophysical properties of the sintered anode are evaluated. It is found that the volume shrinkage occurs along with the self-assembly phenomenon during the sintering process. Sintering at relatively low temperature and high pressure could contribute to the densification of the anode. Compared with the experimental structure, the sintered anode obtained from this study shows a common morphology. Sintering at the nanoscale is beneficial to distribute the functional components equally. Furthermore, the effects of the sintering temperature, sintering pressure and material composition on the volumetric heat capacity and thermal expansion coefficient of the sintered anode are systematically discussed. The predicted thermophysical properties of the anode agree well with the open literature data. Results in this study could provide a guide of the sintering conditions and composition during the experimental studies to obtain the desired properties of the SOFC anode.